A survey on the repair and maintenance cost of machinery at Sime Darby Plantation, Serkam-Kemendore divion for the year 2015 / Abdul Muin Abdul Balim - Abdul Balim, Abdul Muin (Faculty of Plantation and Agrotechnology, 2016)
As the population of the world increases, the demand for cooking fat has steadily increases. One of product that can cope with the demand is palm oil. Although there is no problem with the demand, there is a problem with production. The main factors that limit the production are the availability of land for oil palm planting. One of the available options is to increase efficiency of oil palm production. TIns make the task is very labor intensive and has very low coverage per working day. In the plantation level, to increase the efficiency of production is with the implementation of mechanization and with the implementation of mechanization, the efficiency could be improved. The ratio of work done is said to be 1 to 1.83. Macmne efficiency is crucial to maintain high level of output. Properly maintained and adjusted macmne also reduces field breakdown. The more field downtime incurred the mgher the operating cost and ultimately decrease profit level. The research is done in three parts which are the satisfaction level survey, the repair and maintenance cost model and the division between the internal and external repair done on the machine. The results are illustrated in the form of a graph and table displaying the skewness test result. Efficiency of the machine must be improve and the cost must lowered to increase the profit level of plantation